Preferensi Konsumen Terhadap Atribut Beras Premium - Natasya (Indoensia), Dhea Vida; Setiawan (Indoensia), Budi; Hardana (Indoensia), Andrean Eka (Universitas Tidar, 2024)
Rice is the main staple food for the people of Surakarta City. In fulfilling their rice needs, rice is still supplied from other cities. In addition, there is a loss of labor, time, and cost caused by returning rice products to the rice milling company. The purpose of this study is to determine the combination of rice attribute levels and the order of importance of rice attributes and analyze the relationship between estimated and actual preferences. This research uses a quantitative approach. The technique of determining the sample through quota sampling. Data analysis techniques using Conjoint analysis. The results of the study show that the preferred combination of rice attribute levels is medium quality 1 (low income) or premium (high income), fluffy, lean, non-aromatic, and hermetic. Meanwhile, the order of importance of rice attributes is quality, shape, fullness, aroma, packaging (low income) and quality, fullness, shape, aroma, packaging (high income). The results of the Pearson's R correlation value show a relationship. Suggestions for rice milling companies in order to improve the quality of rice products.